Penerapan Terapi Dzikir untuk Meningkatkan Kualitas Tidur Pada Lansia di Panti Usia Lanjut ‘Aisyiyah Sumber Surakarta - Yayang Muhammad Shidiq; Sitti Rahma Soleman (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Background: The elderly commonly undergo changes encompassing physical, psychological, and biological aspects. One such biological change is altered sleep patterns, resulting in poor sleep quality. Sleep quality disturbances among the elderly can be alleviated through the application of dhikr therapy. Objective: To determine the difference in sleep quality before and after the implementation of dhikr therapy for enhancing sleep quality. Method: This study employed a descriptive design involving 2 female participants, conducted from June 4th to June 10th, 2023, at the 'Aisyiyah Sumber Surakarta elderly care facility. Each participant received 7 consecutive days of intervention. The instrument used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality levels before and after the therapy. Results: Prior to intervention, participant 1 had a sleep quality score of 16 (poor category), and participant 2 scored 11 (poor category). After dhikr therapy, participant 1's sleep quality improved to 10 (poor category), and participant 2 achieved a score of 7 (poor category). Both participants experienced decreased sleep quality scores. Conclusion: Dhikr therapy can enhance sleep quality among the elderly. Despite reduced sleep quality scores post-intervention for both participants, these changes suggest improved sleep quality due to dhikr therapy's application.